2013
DOI: 10.3390/ijms14046614
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neuronal Differentiation of Rat Muscle-Derived Stem Cells in Vitro Using Basic Fibroblast Growth Factor and Ethosuximide

Abstract: Several studies have demonstrated that basic fibroblast growth factor (bFGF) can induce neural differentiation of mesenchymal stem cells. In this study, we investigated the neural differentiation of muscle-derived stem cells (MDSCs) following treatment with bFGF and ethosuximide, a small molecule used as an anticonvulsant in humans. Stem cells isolated from rat skeletal muscle (rMDSCs) were pre-induced by culturing with 25 ng/mL bFGF for 24 h and then were transferred to a medium supplemented with or without 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Donepezil was shown to promote the differentiation of primary NSCs into mature oligodendrocytes at the expense of astrocytes [150], and it was also found to enhance myelin sheath generation in neuron/glia co-cultures [151]. The FDA-approved anti-seizure drug ethosuximide was described to be capable of inducing trans-differentiation of muscle-derived stem cells into Olig2-positive oligodendroglial cells [152]. Whether ethosuximide activity could also be used to re-establish the glial cell balance needs to be shown, keeping in mind that Olig2 expression itself is not restricted to oligodendroglial cells, but is also found in the cytoplasm of astroglia [153].…”
Section: Regulators Of Glia Cell Fate: Avenues To Adjust Aberrant Whimentioning
confidence: 99%
“…Donepezil was shown to promote the differentiation of primary NSCs into mature oligodendrocytes at the expense of astrocytes [150], and it was also found to enhance myelin sheath generation in neuron/glia co-cultures [151]. The FDA-approved anti-seizure drug ethosuximide was described to be capable of inducing trans-differentiation of muscle-derived stem cells into Olig2-positive oligodendroglial cells [152]. Whether ethosuximide activity could also be used to re-establish the glial cell balance needs to be shown, keeping in mind that Olig2 expression itself is not restricted to oligodendroglial cells, but is also found in the cytoplasm of astroglia [153].…”
Section: Regulators Of Glia Cell Fate: Avenues To Adjust Aberrant Whimentioning
confidence: 99%
“…These changes were found in most cells of group 4. Kang et al [ 22 ] investigated the neural differentiation of stem cells derived from muscle followed by treatment with an anticonvulsant and FGF. The morphological changes observed in cultures stimulated with FGF for 24 hours were consistent with GABA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al reported that valproic acid (VA), a histone deacetylase inhibitor used in the treatment of epilepsy, bipolar disorder, led to differentiation of muscle-derived stem cells toward neuronal lineages. Recently, Kang et al demonstrated that fibroblast growth factor (FGF) and ethosuximide, which is used clinically to treat absence seizures in humans, induced neuronal differentiation of muscle-derived stem cells by showing immunohistochemically positive cells for TuJ1, NeuN, and neurofilaments M and H [150]. Further studies to reveal the mechanistic background of the conversion into the neuronal lineage may reveal further potential applications of muscle-derived stem cells, which can easily regenerate and consequently be rapidly expanded ex vivo , for repair of neuronal injuries and treatment of neuronal disorders.…”
Section: Transdifferentiation Of Muscle-derived Stem Cellsmentioning
confidence: 99%